(untitled) (Jurnal Manajemen dan Organisasi, 2019)
Nickel industry is one of the industry that potentially to increase foreign exchange. PT Antam Tbk UBPN Southeast Sulawesi has land area about 169.194,937 m2 with 14.452,85 m2 of buildings in FeNi Plant 3. In producing nickel, PT Antam Tbk UBPN Southeast Sulawesi requires a more optimum layout and material flow pattern. The objective of this research was to analyzed the layout of production and material handling in the FeNi Plant 3. The methods used in this study were relationship analysis of production activity and Assembly Line Balancing. The result showed that the current ferronikel flow layout and flow pattern is shaped a straight line, and efficiency assembly line balansing about 71,25 percent.